2015
DOI: 10.1089/scd.2014.0255
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Transplantation of Human Umbilical Cord Blood Endothelial Progenitor Cells with Immunomagnetic Nanoparticles to Repair Corneal Endothelium Defect

Abstract: Corneal endothelial dysfunction involves progressive corneal edema and loss of visual acuity, which result in the need for corneal transplantation. The global shortage of donor corneas limits the development of the surgery. Reconstruction of a bioengineered corneal endothelium might resolve this problem. Various scaffolds have been used, but poor biocompatibility and degradation limit their applications. In this study, a novel method of targeted cellular transplantation without permanent residence of cell carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 32 publications
0
18
0
4
Order By: Relevance
“…Ju et al reported the differentiation of corneal endothelial like‐cell from rat neural crest cells in vitro . Other stem cell sources such as ES cells , iPS cells , umbilical cord blood cells , and umbilical cord blood endothelial cells also seem promising.…”
Section: Discussionmentioning
confidence: 99%
“…Ju et al reported the differentiation of corneal endothelial like‐cell from rat neural crest cells in vitro . Other stem cell sources such as ES cells , iPS cells , umbilical cord blood cells , and umbilical cord blood endothelial cells also seem promising.…”
Section: Discussionmentioning
confidence: 99%
“…According to different authors, umbilical cords should be collected from full-term infants, ideally delivered by natural birth, from healthy mothers, after an uncomplicated pregnancy, and should be free of hepatitis or human immunodeficiency virus (HIV) infection [42]. In some studies, the authors specify whether they used cords collected from natural births [51][52][53] or cesarean sections [29,[54][55][56][57]. Occasionally, cords from pregnancies of mothers with certain diseases or traits may be required, for example, HUVEC from infants with mothers who developed gestational diabetes have been used for genetic, epigenetic, and proteomic studies of the effects of T2D on EC [58,59].…”
Section: Umbilical Cord Collection and Conservationmentioning
confidence: 99%
“…It has been reported that human umbilical cord blood mesenchymal stem cells, which have been cultured by conditioned medium (LEC-CM) of HLEC, can be induced to differentiate into CECs by simulating the development of the eye. 32 Meanwhile, mature CECs can also provide some inducing factors for undifferentiated CECs by autocrining some regulatory factors. 33,34 At this stage, we induced the differentiation of POMPs using a mixed-conditioned medium of both LEC-CM and HCEC-CM.…”
Section: The Isolation and Characterization Of Cec-like Cellsmentioning
confidence: 99%